Predictors of therapeutic alliance in two treatments for adults with severe and enduring anorexia nervosa. Issue 1 (December 2016) - Stiles-Shields, Colleen; Bamford, Bryony; Touyz, Stephen; Le Grange, Daniel; Hay, Phillipa; Lacey, Hubert
Abstract Background Therapeutic alliance (TA) has been found to be a significant predictor of outcome for patients with severe and enduring anorexia nervosa (SE-AN), accounting for more variance than treatment type. To better understand how to promote TA for this population, the aim of the current study was to investigate predictors of TA in adults with SE-AN. Methods Participants were 63 adult females with SE-AN presenting to an outpatient, multi-site randomized controlled trial conducted at two clinical sites. Participants' perception of the quality of their therapeutic relationship, demographic information, and eating disorder symptomatology were assessed via interview and questionnaire measures. Results Baseline ratings of how successful participants believed treatment would be for them was the only variable to significantly predict early (p = .01), mid (p = .009), and late treatment alliance (p = .03). No other variables investigated predicted the quality of patient rated TA at any point in treatment (ps > .57). Conclusions Results suggest instilling hope in treatment outcome may enhance TA, and in turn, outcomes for patients with SE-AN in outpatient therapy.